2021
DOI: 10.3390/app12010318
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tuned Spring on Vibration Control Performance of Modified Liquid Column Ball Damper

Abstract: This paper reports the theoretical findings of the new modified type of tuned liquid column ball damper (TLCBD), called a tuned liquid column ball spring damper (TLCBSD). In this new modified form, the ball inside the horizontal section of the damper is attached to the spring. Furthermore, two types of this modified version are proposed, known as a tuned liquid column ball spring sliding damper (TLCBSSD) and a tuned liquid column ball spring rolling damper (TLCBSRD). In the former, the rotational motion of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…It can be observed that controlled MDOF structure responses have been improved with TLCD at all loading conditions except 1.95 Hz. This slight increase in the response of the structure equipped with liquid dampers at loading frequencies higher than resonance loading frequency has been reported in the literature [ 15 , 51 ]. It is because the liquid dampers are effective for low frequencies vibration and effective only in the resonance region.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…It can be observed that controlled MDOF structure responses have been improved with TLCD at all loading conditions except 1.95 Hz. This slight increase in the response of the structure equipped with liquid dampers at loading frequencies higher than resonance loading frequency has been reported in the literature [ 15 , 51 ]. It is because the liquid dampers are effective for low frequencies vibration and effective only in the resonance region.…”
Section: Resultssupporting
confidence: 73%
“…These systems are mainly passive, active, semi-active, and hybrid [ 16 – 19 ]. Compared to active, semi-active and hybrid systems, passive damping systems are the most reliable and economical vibration mitigation systems [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Passive-tuned mass and liquid dampers are a popular choice among structural vibration control systems for being reliable, economical, and easy to implement [25]. Passive vibration control devices like tuned liquid column dampers not only signifcantly reduce buildings' vibrations but also can serve as a water storage facility [26]. Particular interest is aroused by the dynamic damper designs based on the efect of collisions [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the life and property damage caused by the earthquakes, different techniques such as vibration damping, and vibration isolation are being used for the seismic protection of a structure [ 1 , 2 , 3 ]. Over the decades, base isolation has been extensively researched and efficiently used for vibration isolation of a structure [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%